REINTERPRETASI LAFADZ MAQRABAH DAN MATRABAH DALAM SURAT AL-BALAD PERSPEKTIF MA’NA CUM MAGHZA - ,, Tarto; Afiah, Syifa (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2025)
This article is motivated by the reality of texts about diversity in interpreting the Qur'an, including in interpreting QS. Al-Balad verses 14-16 which contain information about feeding orphans and the poor. Some commentators understand it as a command to provide for orphans and the poor during times of famine, some interpret it as an effort to spread social justice, and some understand it with the priority/target for distributing aid contained in the words maqrabah and matrabah. This is very relevant to the phenomena that often occur and the conditions that befall this country, namely poverty, misuse of public funds, corruption, inappropriate distribution of aid, the gap between the rich and the poor, hedonism in some people, and injustice for the weak. The author will try to reinterpret QS. Al-Balad verses 14-16 and see the development of interpretations of the verses studied, especially the meaning of maqrabah and matrabah. This research is included in the type of library research. The approach used is the ma'na cum maghza approach from Sahiron Syamsuddin. The results of this study are the words maqrabah and matrabah in QS. Al-Balad verses 14-16 indicate the priority of orphans and poor people who are given assistance, namely: orphans who have closeness (blood relations/place/nationality/humanity), Poor people who are matrabah, namely if associated with the current context, the author found several conditions of people who fall into this category, namely: 1) Homeless or vagrants, 2) Street children, 3) People who live in slums, 4) Uninhabitable housing, 5) Have no income so they often do not eat, 6) People affected by war or political conflict in a country.